Corporate Power and the Philippine Public Sphere The Philippine Daily Inquirer and the NBN-ZTE Scandal of 2007 - Cardenas, Kenneth Lawrence F. (Philippine Social Sciences Review; Volume 62 No.2 July-December 2010, Ed. Eric Manalastas, 2011)
This paper approaches the debate on corporate power through a framework informed by Habermas’s concepts of the legitimation of political orders. It problematizes corporate power as a new political order that needs to extract legitimation from the public, and the agenda-setting power of the mass media as a strategic asset in achieving this end. Through a case study of the Philippine Daily Inquirer’s coverage of a high-profile issue involving both corporate and state malfeasance—the so-called NBN-ZTE scandal—this paper shows that corporate power was portrayed as non-political and outside the realm of public scrutiny, accomplished through three features of the coverage: a low amount of coverage on the theme of corporate malfeasance; the construction of the involved corporation’s identity that emphasized its nationality above all other aspects, including ownership, control, and corporate history; and lastly, the representation of its actions as either devoid of agency, or as the responsibility of other agents. The study also identifies processes and institutions relating to the production of news by the Inquirer and the definition of issues by agents in society, particularly the Philippine Senate and members of the public, which accounted for this portrayal. Finally, the study explores the possibility that the legitimation of corporate power, in the Philippine context, may be achieved by the complete circumvention of the democratic pressures of the public sphere.
Keywords: corporate power